THE EFFECTS ON BIOLOGICAL MATERIALS OF FREEZING AND DRYING BY VACUUM SUBLIMATION : II. EFFECT ON INFLUENZA VIRUS - Greiff, Donald (The Rockefeller University Press, 1954)
The infectivity titre of influenza virus-infected allantoic fluid was determined after a variety of procedures involving cyclic slow freezing and thawing, freezing at various rates with subsequent storage at different temperatures freezing at various rates with subsequent dehydration at various temperatures, and different degrees of dehydration. All these factors were found to influence the survival rate of the virus particles. Five freeze-thaw cycles resulted in a fall in titre from 10(–8.6) to 10(–0.8) cycles 2, 3, and 4 causing much greater losses than cycles 1 and 5. Rapid cooling to –40°C. or slow cooling to –80 or 190°C. did not cause significant titre loss, but rapid cooling to temperatures above –40° or slow cooling to temperatures above –80°C. caused definite titre loss. Loss of titre on storage occurred only at temperatures above –40deg;C. The effect of lyophilization depends both on the preliminary treatment and on the dehydration temperature. Better conservation of titre was obtained after preliminary cooling to –190 or –80°C. than after preliminary cooling to higher temperatures. The most effective sublimation temperatures were 0 and –80°.; the least effective was +20°C. Titre losses in suspensions sublimated at –10, –30, and –60°C. were in general intermediate. No loss in titre occurred after preliminary cooling to –80 or –190°C. and subsequent dehydration at –80 or 0°C. The degree of dehydration definitely affects the survival of virus on storage at 0°C., but sublimation for 4 hours at 0°C. gave complete protection against titre loss on storage at this temperature. Possible explanations of the observations made are suggested, based on known physiochemical phenomena such as supercooling, vitrification, variations in size and shape of ice crystals with different freezing speeds, differential enzyme inactivation, changes in salt concentration, and changes in energy levels.